Agility and Productivity Management in the Manufacturing Industry - Suwanda, Suwanda (SEAN Institute, 2022)
The manufacturing industry is faced with ever-evolving challenges, including rapid changes in technology, global competition and increasing consumer demands. The success of manufacturing companies depends on the extent to which they can manage and increase organizational agility to face market changes and how efficient they are in increasing productivity. This research aims to analyze and improve agility and productivity management in the manufacturing industry. The results of this research show that the implementation of agility and productivity management strategies in the manufacturing industry has a significant positive impact. Through the use of advanced technology, automation, and employee training, companies can improve operational efficiency and workforce productivity. Flexibility in product design, efficient supply chain management and integrated production plans support companies in responding to changes in market demand more quickly and effectively. Smart inventory management has also been proven to minimize storage costs while maintaining raw material availability. Continuous performance measurement and application of continuous improvement principles help create an environment that is responsive to change and innovation.